Evidence for very recent melt-water and debris flow activity in gullies in a young mid-latitude crater on Mars - Johnsson, Andreas; Reiss, Dennis; Hauber, Ernst; Hiesinger, H.; Zanetti, M. (Icarus, 2014)
Terrestrial debris flows and their deposits are mainly studied and monitored because of their hazardous nature. On Mars they may serve as geomorphologic indicators of transient liquid water. We compared the morphology of debris flow-like deposits within a young (0.2 Ma) mid-latitude crater on Mars with debris flow fans on Svalbard as possible terrestrial analogues. It was our objective to constrain whether dry granular flow or processes related to water-saturation at or close to the surface were responsible for the formation of the deposits within the crater.We found that the morphological attributes of the deposits on Mars are very similar to debris flows in Svalbard and include overlapping terminal lobes, debris tongues and snouts, debris-flow fans, scoured channels with medial deposits (debris plugs), and clearly defined lateral deposits (levées). Furthermore, the interior crater walls display a range of landforms indicating aspect-dependent degradation, ranging from debris flow-dominated pole-facing slopes, to east-andwest- facing single channel gullies and north-facing talus cones (granular flow). Our findings suggest that the debris flows are not related to impact-induced heating and release of meltwater. We further suggest that degradation of a latitude dependent dust–ice mantling unit may only have played a minor role in this youthful terrain. Instead, we propose that the debris flows are mainly formed by melting of very recent snow deposits after the termination of the last martian ice-age. As such they may represent some of the most recent geomorphological indicators of transient liquid water in the martian mid-latitudes. The distinct north–south asymmetry in degradation further demonstrates that insolation-controlled slope processes are surprisingly efficient on Mars during the last <1 Myr.